Modelling Migratory Pinch Points and Connectivity of Pygmy Blue Whale Using Circuit Theory: A Case Study of Savu Sea, Indonesia - Muhammad Shulhan Jihadi; Muhammad Zainuri; Virginia Andrews- Goff; Rikha Widiaratih; Kunarso Kunarso; Elis Indrayanti (Ilmu Kelautan)
Blue whale and their subspecies is an endangered whale species that needs to be conserved by protecting their important habitat and migration corridor. Research about designing and modelling blue whale habitat for marine protected area has been done many times. However, incorporation of connectivity in marine protected areas design and management has been limited due to the complexity of methods used to model connectivity, therefore the implementation among practitioners is inconsistent. An alternative method to model connectivity of pygmy blue whale habitat is discussed through a combination of maximum entropy model and circuit theory. The habitat suitability models were made using satellite-tagged pygmy blue whale data (2012-2016) and oceanographic variables, such as sea surface temperature, chlorophyll, salinity, bathymetry, and seafloor geomorphology for four season that is March-April-May (MAM), June-July-August (JJA), September-October-November (SON), and December-January-February (DJF). The habitat suitability model shows different importance of environmental variables in their preference of habitat in each season, with distance from slope as the most influential parameter during the migration season (54.4% for MAM, 37.8% for SON), mean climatological chlorophyll during winter (31%), and mean climatological sea surface temperature during summer (54.7%). Habitat suitability result were then used to model connectivity, assuming that the whales migrate during MAM and SON. The migration model from Omniscape showed some pinch point, such as Sumba-Sape strait, Alor strait, Rote strait, Ombai strait. These pinch points can be seen as corridors with high potential of pygmy blue whale migration or high connectivity, therefore this area could become priority for conservation.